2016
DOI: 10.1136/jramc-2015-000614
|View full text |Cite
|
Sign up to set email alerts
|

Appendicitis in a deployed military setting: diagnosis, management and impact on the fighting force

Abstract: Diagnostic imaging will be limited in future conflicts and reliance on clinical judgement will be necessary. Military clinicians may need to accept higher rates of NA, as prolonged observation may not be possible. CT scanning should be used to a greater extent when available. A conservative management strategy for appendicitis with appropriate antibiotics should be considered in the event of delayed transfer to a surgical facility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…The 133 included studies collectively reported on more than 9.1 million surgical procedures (median per study, 894 [IQR, 97-4259]) and more than 11.4 million participants (median per study, 989 [IQR, 257-6857]) from 63 LMICs . Of all 133 LMICs, we found studies from 15 of all 29 low-income countries (51.7%), 25 of all 50 lower-middle–income countries (50.0%), and 23 of all 55 upper-middle–income countries (41.8%) . Fourteen studies (10.5%) were multinational …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 133 included studies collectively reported on more than 9.1 million surgical procedures (median per study, 894 [IQR, 97-4259]) and more than 11.4 million participants (median per study, 989 [IQR, 257-6857]) from 63 LMICs . Of all 133 LMICs, we found studies from 15 of all 29 low-income countries (51.7%), 25 of all 50 lower-middle–income countries (50.0%), and 23 of all 55 upper-middle–income countries (41.8%) . Fourteen studies (10.5%) were multinational …”
Section: Resultsmentioning
confidence: 99%
“…Most studies (115 [86.5%]) were published in 2010 or after, with a marked increase in the number of included studies per year. Most articles were written in English (126 [94.7%]) . Health care settings were hospital based or secondary care in 93 studies (69.9%) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations